Economic importance of ensuring the welfare for farm pigs - Cristina-Stefania Matache (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Lately it speaks a lot about ensuring animal welfare and about the influence of the environment on life and on animal performance. Pig farming depends heavily on the environment because pigs needs all the elements for the comfort (enough space for sleep and movement, enough food depending on nutritional requirements for the animal category, water ad libitum, and health insurance) for growth and to deposit bonus. When these needs are not respected, pigs begin to lose weight and that affect the production and the economic efficiency of the farm. The purpose of this study is to provide necessary information that have an important influence on the production and on the economic efficiency of the farm when animal requirements are not met, but also to known and combating stress factors. The material is addressed to farmers and both to those who want to set up a pig farm.
Keywords: 330; welfare; daily average gain; food; growth conditions; microclimate